As compact city planning rolls on, a look back: lessons from Sydney and Perth. Issue 2 (3rd April 2017) - Crommelin, Laura; Bunker, Raymond; Troy, Laurence; Randolph, Bill; Easthope, Hazel; Pinnegar, Simon
ABSTRACT: This paper categorises and compares the policy frameworks that have encouraged higher density urban renewal in Sydney and Perth since the mid-2000s, which reflect the 'compact city' model that has become international urban planning orthodoxy. The policies can be grouped into four broad categories: (i) metropolitan strategies; (ii) transport and infrastructure plans; (iii) legislation creating development corporations; and (iv) planning system reforms. By comparing these policies, the paper identifies some key similarities and differences in how the compact city model has been adopted in Sydney and Perth. The most significant similarities are the changing power relationships reshaping urban planning and governance, and the ongoing challenges of integrating land-use and transport planning. The paper concludes with some brief commentary on the challenge these two issues pose for the next decade of compact planning, particularly for strategic planning bodies like the Greater Sydney Commission and the Western Australian Planning Commission.